The role and research progress of serine metabolism in tumor cells - Lyu, Hanning; Bao, Shuchang; Cai, Lingyun; Wang, Mengke; Liu, Yuxin; Sun, Yang; Hu, Xiaoyang (Frontiers in Oncology, 2025)
Serine is crucial for tumor initiation, progression, and adaptive immunity. Metabolic pathways for serine synthesis, acquisition, and utilization in tumors and tumor-associated cells are influenced by various physiological factors and the tumor microenvironment, leading to metabolic reprogramming and amplification. Excessive serine metabolism promotes abnormal macromolecule biosynthesis, mitochondrial dysfunction, and epigenetic modifications, driving malignant transformation, proliferation, metastasis, immune suppression, and drug resistance in tumor cells. Restricting dietary serine intake or reducing the expression of serine synthetic enzymes can effectively slow tumor growth and extend patient survival. Consequently, targeting serine metabolism has emerged as a novel and promising research focus in cancer research. This paper reviews serine metabolic pathways and their roles in tumor development. It summarizes the influencing factors of serine metabolism. The article explores the significance of serine synthesis and metabolizing enzymes, along with related biomarkers, in tumor diagnosis and treatment, providing new insights for developing targeted therapies that modulate serine metabolism in cancer.